Mechanisms of mitophagy in cellular homeostasis, physiology and pathology - Palikaras, K.; Lionaki, E.; Tavernarakis, N. (Nat Cell Biol, 2018)
Mitophagy is an evolutionarily conserved cellular process to remove dysfunctional or superfluous mitochondria, thus fine-tuning mitochondrial number and preserving energy metabolism. In this Review, we survey recent advances towards elucidating the molecular mechanisms that mediate mitochondrial elimination and the signalling pathways that govern mitophagy. We consider the contributions of mitophagy in physiological and pathological contexts and discuss emerging findings, highlighting the potential value of mitophagy modulation in therapeutic intervention.
Palikaras, KonstantinosLionaki, EiriniTavernarakis, NektariosengReviewEnglandNat Cell Biol. 2018 Sep;20(9):1013-1022. doi: 10.1038/s41556-018-0176-2. Epub 2018 Aug 28.
Keywords: *Mitophagy; Animals; Apoptosis Regulatory Proteins/metabolism; Autophagy-Related Proteins/metabolism; homeostasis; Humans; Mitochondria/*metabolism/pathology; Mitochondrial Proteins/*metabolism; Protein Kinases/metabolism; signal transduction; Ubiquitin-Protein Ligases/metabolism